3
$\begingroup$

I solved this equation for $y$ by inspection and confirmed it with Wolfram Alpha -

$y^2 - yx - y + x = 0$

I got the values $y = 1$ and $y = x$

However I was wondering is there a formal method for solving it? I expressed it as a polynomial -

$y^2 + (-1 - x)y + x = 0$

and used the quadratic formula but it just left me with an awkward expression involving powers of $x$ and a square root...no $y = 1$ and $y = x$ which is what I was looking for...

So how would I go about solving this formally?

$\endgroup$
  • $\begingroup$ Wolfram Alpha itself gives factorisation $\endgroup$ – user171358 Oct 23 '14 at 14:47
  • $\begingroup$ I just do not understand--how can you be asking questions about rings, metric spaces, topology, and then this sort of basic algebra all together ... $\endgroup$ – meonstackexchange Oct 24 '14 at 1:21
5
$\begingroup$

$$y^2-(x+1)y+x=0$$ First method - using the quadratic formula: $$y_{1,2}=\frac{x+1\pm\sqrt{(x+1)^2-4x}}{2}=\frac{x+1\pm\sqrt{(x-1)^2}}{2}=\frac{(x+1)\pm(x-1)}{2}$$ Thus the solutions are $y=x$ or $y=1$.

Second method - taking common factors: $$y^2-yx-y+x=y(y-x)-1(y-x)=(y-1)(y-x)=0$$ Thus the solutions are $y=x$ or $y=1$.

| cite | improve this answer | |
$\endgroup$
  • 2
    $\begingroup$ Your first line should read $y^2 - (x + 1)y + x = 0$. $\endgroup$ – N. F. Taussig Oct 23 '14 at 14:49
  • $\begingroup$ @N.F.Taussig, thanks for noticing, I'll edit. $\endgroup$ – Galc127 Oct 23 '14 at 14:50
6
$\begingroup$

Factor by grouping: $y^2 - yx - y + x = y(y-x)-(y-x)=(y-x)(y-1)=0$ So either $y-x=0$ or $y-1=0$. The result follows.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

You can complete the square to get $$\left( y-\frac{1+x}2\right)^2=\frac{(1-x)^2}4$$ from which the solutions are obvious.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Just don't forget that if $a^2=b^2$, then $a=\pm{b}$, so there are two options to check. Also, you should write RHS as $\displaystyle \left(\frac{1-x}{2}\right)^2$ $\endgroup$ – Galc127 Oct 23 '14 at 14:46
  • 1
    $\begingroup$ @Galc127 that's why I said solutionS. $\endgroup$ – Nemo Oct 23 '14 at 14:54
  • $\begingroup$ my comment is just for noting that someone might forget. $\endgroup$ – Galc127 Oct 23 '14 at 14:55
1
$\begingroup$

Well, check again.

For $y^2+(−1−x)y+x=0$ with $y$ as the quadratic variable.

The quadratic formula with $b$ as $(-1-x)$, $a$ as $1$, and $c$ as $x$ tells that the roots are $$y_{1,2}=\displaystyle \frac{(1+x) \pm \sqrt{1+x^2+2x - 4x}}{2}=\frac{(1+x)\pm\sqrt{1+x^2-2x}}{2}=\frac{(1+x) \pm{1-x}}{2}$$ Hence the solutions are $$y_1=\frac{1+x+1-x}{2}=1 \ , \ y_2=\frac{1+x-1+x}{2}=x$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.